Dementia-Related Education and Support Service Availability, Accessibility, and Use in Rural Areas: Barriers and Solutions. Issue 4 (24th December 2020) - Bayly, Melanie; Morgan, Debra; Froehlich Chow, Amanda; Kosteniuk, Julie; Elliot, Valerie
ABSTRACT: This scoping review mapped and synthesized published literature related to education and support services for individuals with dementia and their caregivers living rurally. Specifically, we investigated education and support service needs, availability and use of services, barriers to service access and use, and solutions to these barriers. Empirical, English-language articles (2, 381) were identified within MEDLINE, CINAHL, PSYCINFO, and EMBASE. Articles were screened according to Arksey and O'Malley's (2005) five-stage scoping review methodology and the recommendations of Levac et al. (2010). Findings suggest limited availability of rural dementia-related support and education services, particularly respite care and day programs. Service use varied across studies, with barriers including low knowledge regarding services, practicality, and resource issues (e.g., transportation, financial), values and beliefs, stigma, and negative perceptions of services. Solutions included tailored and person-centred services, technological service provision, accessibility assistance, inter-organization collaboration, education regarding services, and having a "point of entry" to service use.